The role of community dynamics on child wellbeing in the context of climate change in the Mwanza Region, Tanzania - Joseph, Laurent (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2024)
The study explored the relationship between community dynamics and child wellbeing in the context of climate change in two districts, Nyamagana and Ilemela, found in the Mwanza Region in Tanzania. This study used a mixed methods research design with 458 participants purposively selected through systematic random sampling. On the other hand, the study applied mixed methods research design (MMRD), which incorporated questionnaires, focus group discussions, and key informant interviews (KII) as data collection methods. The findings established that climate change negatively impacted children's wellbeing through higher temperatures, erratic rainfall, food scarcity, disrupted schooling, and increased diseases. The community dynamics identified that enhanced child wellbeing were strong local resilience and coping strategies, support groups, educational initiatives, and environmental conservation commitment. The study explored a range of community-driven strategies and interventions to enhance child wellbeing, including local adaptation practices, education, improved healthcare, infrastructure development, water conservation, and early warning systems. The research also underlines climate-resilient infrastructure as one of the explicit elements towards tackling climate-related challenges and promoting child wellbeing. The research provides priceless insights and recommendations to communities, stakeholders, and policymakers on tackling climate-related challenges affecting child wellbeing in the Mwanza region and the world at large.JEL ClassificationÂ O13; Q00; Q54To cite this article: Joseph, L. (2024). The role of community dynamics on child wellbeing in the context of climate change in the Mwanza Region, Tanzania. Journal of Socioeconomics and Development, 7(1), 89-103. https://doi.org/10.31328/jsed.v7i1.5527